Islamization of knowledge: a comparative analysis of the conceptions of Al-Attas and Al-Faruqi - Hashim, Rosnani; Rossidy, Imron (IIUM Press, 2000)
There has been a lot of discussion and debate on the issue of Islamization of Contemporary Knowledge among Muslim intellectuals. Two Muslim thinkers, namely al-Attas and al-Faruqi were foremost in the attempt to conceptualise the problem of the Muslim ummah and the issue of Islamization of knowledge as an epistemology and socio-political solution. This article aims to examine, compare and analyse the ideas of both scholars with respect to the various interpretations of the concept of Islamization of knowledge their definition of the concept, their philosophical framework, and their methodology for achieving goals of Islamization. It aims at understanding the similarities and differences and the strengths and weaknesses of their conceptions, philosophical framework and methodology. This paper also explores the possibility of reconciliation between their ideas in the hope of further advancing the cause of Islamization of knowledge.